Modu : optimizing the product line - Sawhney, Mohanbir S., (SAGE knowledge. Cases., 2016)
Israeli entrepreneur and inventor Dov Moran envisioned the creation of a mobile device that was a small, stand-alone, fully functional mobile phone that could be slipped into a variety of enclosures, or 'jackets,' that would provide added functionality and better reflect the personalities of its users. As the development of the Modu phone began to take shape, Moran and his team decided that to ensure the success of the new phone's much anticipated launch, Modu would develop and market the accessory jackets itself. This case study examines how they went about this process.